Features of Raman spectra of mechanically activated graphite. (March 2019) - Chaika, V.A.; Savin, V.V.; Savina, L.A.; Osadchy, A.V.; Rybin, M.G.
Abstract: The prolonged mechanoactivation treatment (MAT) of graphite and carbon materials causes nonequilibrium processes, accompanied by stepwise changes in the characteristics of the structure of the material and its phase constituents. Using the techniques of electron microscopic analysis and Raman spectroscopy, the research task was to study the effect of short-term high-energy MAT on the possibility and regularity (sequence) of the transformation of chemical bonds between carbon atoms in the produced micro- and nanopowder materials. To compare the rate of change, graphite MPG-7 was processed for no more than an hour at 1000 and 1500 rpm. The changes were evaluated not only by the shift of the Raman spectrum lines, but also by the structural ordering of the substance and the degree of disorder, by thedegree ofamorphization. Similar nonlinear parameter changes for the two processing modes are detected. It is shown that treatment with less energy for an hour leads to a greater accumulation of energy in the material, which is reflected in the internal pressure corresponding to the difference Raman spectrum lines (S1-D1).